2017
DOI: 10.1371/journal.pone.0188137
|View full text |Cite
|
Sign up to set email alerts
|

Replacing methyl bromide with a combination of 1,3-dichloropropene and metam sodium for cucumber production in China

Abstract: The combination of 1,3-dichloropropene (1,3-D) and metam sodium (MNa) is a potential resource to replace methyl bromide (MB) as a soil fumigant. The efficacy of 1,3-D+MNa as a crucial factor to limit soil-borne pests was evaluated in one laboratory experiment and two cucumber greenhouse studies conducted in commercial operations. Laboratory results revealed that 1,3-D and MNa (10+20 mg a.i. kg−1 soil) provided the best complementary control of the root-knot nematode, Fusarium oxysporum and two species of weed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…These results are supported by the fact that the highest pepper yields and root weights were also found in the MS and LR + MS treatments. This could indicate that metam sodium is more effective as a fungicide and nematicide [1,3] than plant extracts (LQ and LR), which did not show either nematicidal [43] or fungicidal activity. These results are opposite to those observed in vitro by Osorio et al [16] and Vogt et al [17], who showed antifungal activity of Larrea spp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are supported by the fact that the highest pepper yields and root weights were also found in the MS and LR + MS treatments. This could indicate that metam sodium is more effective as a fungicide and nematicide [1,3] than plant extracts (LQ and LR), which did not show either nematicidal [43] or fungicidal activity. These results are opposite to those observed in vitro by Osorio et al [16] and Vogt et al [17], who showed antifungal activity of Larrea spp.…”
Section: Discussionmentioning
confidence: 98%
“…Metam sodium (sodium N-methyldithiocarbamate) is an organosulfur soil fumigant considered to be moderately hazardous (toxicity class II) by the World Health Organization that is applied nowadays [2,3]. Several studies have reported the efficiency of MS against root-knot nematodes and fungal pathogens, such as Fusarium spp., Pythium spp., and Rhizoctonia solani, when used either alone or in combination with other pesticides [1,3]. Nevertheless, MS can affect the soil community structure due to its inhibitory effect on Gram-negative bacteria and fungi [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nematicides, such as avermectin [29], methyl bromide [30], and metam sodium [31], exhibit nematicidal or fumigant activity against RKNs, and most of them are toxic to animals and unfriendly to the environment [32][33][34]. Many RKNs have developed resistance to these nematicides that are continuously applied in the agricultural field for a long period worldwide [35].…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-20th century, synthetic chemicals have been used to control many plant diseases including a broad spectrum soil fumigant, methyl bromide (MeBr) [ 17 , 18 , 19 ]. Since then, MeBr has been heavily applied worldwide primarily to control soil-borne pathogens as well as the nematodes [ 20 ]. For example, five million kg of MeBr were used only in California in the year 2000 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%